A discourse analysis of instructions of making beverages in english and vietnamese - Nguyễn,Xuân Tích (ĐHĐN., 2015)
This study made an investigation into the instructions of making beverages in English and Vietnamese in an attempt to discover the layout, syntactic feature, lexical choice and cohesive devices. Then based on the results of comparison, this study found out the similarities and differences between instructions of making beverages in English and those in Vietnamese. The findings of this study were presented based on a survey of 20 instructions of making beverages in English and another 20 ones in Vietnamese taken from videos of making beverages on the Internet and television. The study found out the three main components in the layout of instructions in both languages including the introduction, the process and the summary. In aspect of syntactic features, the types of sentences, sentence structures, noun phrases and adverbial clauses in both languages were analyzed. In regard to lexical choice, there were three typical themes in instructions in both languages analyzed consisting of quantity denoting words, tool denoting words and activity denoting words. The study also found out the cohesive devices of the instructions of making beverages in both languages containing grammartical devices including reference and conjunction as well as lexical devices consisting of repetition and synonym. Basing on the results of analyzing and contrasting the instructions of making beverages in English and Vietnamese, the study summarized and came to a number of conclusions and implications for teaching and learning language